2019
DOI: 10.1038/s41598-019-47642-2
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing versus methylation-specific PCR for assessment of MGMT methylation in tumor and blood samples of glioblastoma patients

Abstract: Circulating biomarkers in blood may provide an interesting alternative to risky tissue biopsies in the diagnosis and follow-up of glioblastoma patients. We have assessed MGMT methylation status in blood and tissue samples from unresected glioblastoma patients who had been included in the randomized GENOM-009 trial. Paired blood and tissue samples were assessed by methylation-specific PCR (MSP) and pyrosequencing (PYR). After establishing the minimum PYR cut-off that could yield a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…TCGA uses the Infinium Methylation Assay (https://www.illumina.com/science/technology/microarray/ infinium-methylation-assay.html) to determine MGMT promoter methylation status. [40][41][42] Infinium Methylation Assays are an immunofluorescence method that uses next-generation highthroughput microchip arrays and probes. While these methods have been reported to be more sensitive and specific than the most widely available clinical assays, they require pre-existing probes to detect specific methylation sites.…”
Section: Discussionmentioning
confidence: 99%
“…TCGA uses the Infinium Methylation Assay (https://www.illumina.com/science/technology/microarray/ infinium-methylation-assay.html) to determine MGMT promoter methylation status. [40][41][42] Infinium Methylation Assays are an immunofluorescence method that uses next-generation highthroughput microchip arrays and probes. While these methods have been reported to be more sensitive and specific than the most widely available clinical assays, they require pre-existing probes to detect specific methylation sites.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrosequencing is the most commonly used quantitative approach and provides real-time quantitative data on the methylation status of multiple CpGs within an amplicon. Several articles have reported that it can detect cfDNA in certain tumor types [37][38][39]. However, due to its sensitivity, it can only detect methylated alleles of not less than 5% at most and its application in the detection of tumor cfDNA methylation is limited.…”
Section: Bisulfite Conversion-based Methodsmentioning
confidence: 99%
“…Sanger sequencing of the Cytosine-Guanine dinucleotide (CpG) sites 74-98 within the MGMT promotor region as previously described 9,10 . Methylation of each individual CpG site was defined as ratio of cytosine/thymine peak > 50%.…”
Section: Mgmt Promotor Methylation and Molecular Markers Mgmt Promotmentioning
confidence: 99%